2021
DOI: 10.3390/metabo11110792
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism, HDACs, and HDAC Inhibitors: A Systems Biology Perspective

Abstract: Histone deacetylases (HDACs) are epigenetic enzymes that play a central role in gene regulation and are sensitive to the metabolic state of the cell. The cross talk between metabolism and histone acetylation impacts numerous biological processes including development and immune function. HDAC inhibitors are being explored for treating cancers, viral infections, inflammation, neurodegenerative diseases, and metabolic disorders. However, how HDAC inhibitors impact cellular metabolism and how metabolism influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…In agreement with previous reports, the present study observed that LSC-like cell lines and primary CD34 + AML progenitor cells were moderately susceptible to the cytotoxicity of chidamide. Recent studies found that HDACs might have important roles outside of transcriptional modulation, such as impacting the metabolic process [ 24 , 25 ]. Moreover, the pharmacological blocking of HDAC activity impacts various metabolic processes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with previous reports, the present study observed that LSC-like cell lines and primary CD34 + AML progenitor cells were moderately susceptible to the cytotoxicity of chidamide. Recent studies found that HDACs might have important roles outside of transcriptional modulation, such as impacting the metabolic process [ 24 , 25 ]. Moreover, the pharmacological blocking of HDAC activity impacts various metabolic processes [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDACs disturb energy metabolism by regulating epigenome modifiers [ 33 ]. Inhibition of HDAC can improve metabolically disturbed adipose, liver, muscle, and cardiac tissue [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain postbiotics exert antitumor activity, including selective cytotoxicity against tumor cells suggesting their therapeutic potential (Figure 1 )[ 5 ]. For example, SCFAs are well-known inhibitors of epigenetic enzymes histone deacetylases, which play a central role in gene regulation; thus, SCFAs have the ability to induce cell cycle arrest, and/or apoptosis in many cancer cell lines[ 37 ]. Cell-free supernatants (CFS) of different Lactobacillus and Bifidobacterium strains have been shown to induce apoptosis or inhibit proliferation of CRC cell lines[ 38 - 40 ].…”
Section: Postbioticsmentioning
confidence: 99%